2005
DOI: 10.1007/s00422-005-0030-z
|View full text |Cite
|
Sign up to set email alerts
|

Learning invariant object recognition in the visual system with continuous transformations

Abstract: The cerebral cortex utilizes spatiotemporal continuity in the world to help build invariant representations. In vision, these might be representations of objects. The temporal continuity typical of objects has been used in an associative learning rule with a short-term memory trace to help build invariant object representations. In this paper, we show that spatial continuity can also provide a basis for helping a system to self-organize invariant representations. We introduce a new learning paradigm "continuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(99 citation statements)
references
References 39 publications
2
97
0
Order By: Relevance
“…Future work involves testing on a larger number of stimuli, and to extend the model to tackle the important challenge of object invariance (cf. [12]). …”
Section: Resultsmentioning
confidence: 99%
“…Future work involves testing on a larger number of stimuli, and to extend the model to tackle the important challenge of object invariance (cf. [12]). …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly the literature on visual perceptual learning has shown that learning can be surprisingly specific to the precise retinal location of the task stimulus (Fahle 2005). The most influential model of translation invariant object recognition is the so-called trace model (Stringer et al 2006), which assumes that this ability actually depends on learning the activity caused by the same stimulus being shown at many different locations; invariant recognition then emerges at a higher level by learning that these different activations are caused by the same object. Perhaps this is what happens when we learn a tune.…”
Section: Discussionmentioning
confidence: 99%
“…] Similar results have also been obtained in a hierarchical feedforward network where each layer operates as a competitive network . This network thus captures many of the properties of our hierarchical model of invariant visual object recognition in the ventral visual stream (Elliffe et al 2002;Rolls 1992;Rolls and Deco 2002;Rolls and Milward 2000;Rolls and Stringer 2001, 2006a, 2006bStringer et al 2006;Rolls 2000, 2002;Wallis and Rolls 1997), but incorporates in addition a foveal magnification factor and top^down projections with a dorsal visual stream so that attentional effects can be studied, as shown in figure 7. LGNÐretinal input Figure 7.…”
Section: Change Blindness and Inattentional Blindnessmentioning
confidence: 99%